АНАЛІЗ ДОВГОСТРОКОВИХ ЗМІН РІЗНOМАНІТНОСТІ БЕНТОСУ В ЛИСЯЧІЙ БУХТІ (ПІВДЕННО-СХІДНЕ УЗБЕРЕЖЖЯ КРИМУ) - Мазлумян, С. А.; Болтачова, Н. О.; Колеснікова, О. А. (Marine Ecological Journal, 2023)
The study of qualitative and quantitative characteristics of macrozoobenthos inhabiting the depth from 1 to 10 m was conducted in the Lysia bay (south-eastern Crimea) in 1998. Data on the benthos biodiversity obtained in 1973 and in 1998 are compared. It was found that taxonomic structure of Chamelea gallina community has substantially changed the average numbers and biomass increased about 20 times. To assess species diversity, Shannon-Wiener and Simpson indices, Berger-Parker dominance index, Pielou evenness index and Margalef' species richness index were used along with the method for comparison of k-dominance curves. Obtained results point out that compared with 1973 in 1998 the biodiversity decreased almost at all investigated depths. Possible explanation may root in the increased eutrophication and partly in the environmental changes.